The Role of Whistleblowing as a Mechanism to Combat State Capture: A Case from the Global South: A Case from the Global South - Radulovic, Ugljesa (NBP. Nauka, bezbednosti, policija, 2023)
State capture is a highly problematic phenomenon, with it entailing collusion practices between state functionaries and private individuals to repurpose the state for their own gain. It creeps up in vulnerable states, those that are developing or are undergoing a transition. When it manifests, it drives those vulnerable states to fragility, turning them into vehicles for predation with severely negative consequences for the state’s citizens. South Africa was plagued by state capture whilst under the leadership of Jacob Zuma (2009-2018). State-owned enterprises were looted, government contracts were manipulated, and structures intended to serve the public good were abused at the behest of the wrongdoers. This came to the fore because of the disclosures of whistleblowers, who reported the wrongdoing to parties that were able to effect action. They exposed a complex system of collusion, highlighting to the South African public how comprised the state had become. Their actions ultimately led to the removal of Jacob Zuma as president of South Africa, leading to the re-democratization of South Africa. This case from the Global South has indicated that the use of whistleblowing as a mechanism to combat state capture could very well be effective. Therefore, this paper argues that whistleblowing should be encouraged, the world over, in order to expose the actions of the corrupted and the corruptors. However, when promoting the use of whistleblowing as an ethical check, adequate legislative protection for whistleblowers needs to exist, as does the cooperation of the state and civil society when supporting whistleblowers.
Keywords: state capture; whistleblowing; South Africa